Temporal trends in characteristics and outcome of heart failure patients with and without significant coronary artery disease - Entela Bollano; Björn Redfors; Araz Rawshani; Dimitrios Venetsanos; Sebastian Völz; Oskar Angerås; Charlotta Ljungman; Joakim Alfredsson; Tomas Jernberg; Truls Råmunddal; Petur Petursson; J. Gustav Smith; et al. (ESC Heart Failure)
Abstract Aims Ischaemic coronary artery disease (CAD) remains the leading cause of mortality globally due to sudden death and heart failure (HF). Invasive coronary angiography (CAG) is the gold standard for evaluating the presence and severity of CAD. Our objective was to assess temporal trends in CAG utilization, patient characteristics, and prognosis in HF patients undergoing CAG at a national level. Methods and results We used data from the Swedish Coronary Angiography and Angioplasty Registry. Data on all patients undergoing CAG for HF indication in Sweden between 2000 and 2018 were collected and analysed. Long‐term survival was estimated with multivariable Cox proportional hazards regression adjusted for differences in patient characteristics. In total, 22 457 patients (73% men) with mean age 64.2 ± 11.3 years were included in the study. The patients were increasingly older with more comorbidities over time. The number of CAG specifically for HF indication increased by 5.5% per calendar year (P < 0.001). No such increase was seen for indications angina pectoris and ST‐elevation myocardial infarction. A normal CAG or non‐obstructive CAD was reported in 63.2% (HF‐NCAD), and 36.8% had >50% diameter stenosis in one or more coronary arteries (HF‐CAD). The median follow‐up time was 3.6 years in HF‐CAD and 5 years in HF‐NCAD. Age and sex‐adjusted survival improved linearly by 1.3% per calendar year in all patients. Compared with HF‐NCAD, long‐term mortality was higher in HF‐CAD patients. The risk of death increased with the increasing severity of CAD. Compared with HF‐NCAD, the risk estimate in patients with a single‐vessel disease was higher [hazard ratio (HR) 1.3; 95% confidence interval (CI) 1.20–1.41; P < 0.001], a multivessel disease without the involvement of left main coronary artery (HR 1.72; 95% CI 1.58–1.88; P < 0.001), and with left main disease (HR 2.02; 95% CI 1.88–2.18; P < 0.001). The number of HF patients undergoing revascularization with percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG) increased by 7.5% (P < 0.001) per calendar year. The majority (53.4%) of HF‐CAD patients were treated medically, while a minority (46.6%) were referred for revascularization with PCI or CABG. Compared with patients treated with PCI, the proportion of patients treated medically or with CABG decreased substantially (P < 0.001). Conclusions Over 18 years, the number of patients with HF undergoing CAG has increased substantially. Expanded utilization of CAG increased the number of HF patients treated with percutaneous coronary intervention and coronary artery bypass surgery. Long‐term survival improved in all HF patients despite a steady increase of elderly patients with comorbidities.